Determinants Of Capital Structure: Study On Food And Beverage Sector Listed On IDX - Arianti, Septiana; Cahyaningtyas, Fadilla (CV. Inara, 2022)
In the sub-sector of food and beverage, capital structure is the most important thing in its operational activities. So it is such a great deal for the company to develop a good capital structure so that its operational activities run smoothly. This research was done on purpose to help explaining what factors gives a major influence on the structure of capital of the food and beverage companies. The method used is a quantitative method in the form of an associative where the sample applied is 10 companies within a period of 3 years, from 2018 to 2020. The technique of data collection is applying the technique of documentation. To test the hypothesis through analysis of multiple linear regression that previously tested in the help of the test of classical assumption.